Containers in Montevideo: a Multi source Image Dataset - Laguna, Rodrigo (2021)
This work presents Clean-Dirty Containers in Montevideo (CDCM), a novel dataset for detection and classi cation of residue con-tainers. Images were collected from several sources, including Google Street View, Social Networks and smarthpone taken photos. The dataset is publicly available under a Creative Commons License.